THE MEASURE OF ALL GODS: RELIGIOUS PARADIGMS OF THE ANTIQUITY AS ANTHROPOLOGICAL INVARIANTS - A. V. Halapsis (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose of the article is the reconstruction of ancient Greek and ancient Roman models of religiosity as anthropological invariants that determine the patterns of thinking and being of subsequent eras. Theoretical basis. The author applied the statement of Protagoras that "Man is the measure of all things" to the reconstruction of the religious sphere of culture. I proceed from the fact that each historical community has a set of inherent ideas about the principles of reality, which found unique "universes of meanings". The historical space acquires anthropological properties that determine the specific mythology of the respective societies, as well as their spiritual successors. In particular, the religious models of ancient Greece and ancient Rome had a huge influence on formation of the worldview of the Christian civilization of the West. Originality. Multiplicity of the Olympic mythology contributed to the diversity of the expression forms of the Greek genius, which manifested itself in different fields of cultural activity, not reducible to political, philosophical or religious unity. The poverty of Roman mythology was compensated by a clear awareness of the unity of the community, which for all historical vicissitudes had always remained an unchanging ideal, and which was conceived as a reflection of the unity of the heavens. These two approaches to the divine predetermined the formation of two interacting, but conceptually different anthropological paradigms of Antiquity. Conclusions. Western concepts of divinity are invariants of two basic theological concepts – "Greek" (naturalism and paganism) and "Roman" (transcendentalism and henotheism). These are ideal types, so these two tendencies can co-exist in one society. The Roman trend continued to be realized by the anti-Roman religion, which took Roman forms and Roman name. Iconoclasm was a Byzantine version of the Reformation, promoted by the Isaurian emperors and failed due to the strong Hellenistic naturalistic lobby. Modern "Romans" are trying to get rid of the last elements of religious naturalism, and modern "Greeks" are trying to preserve the Hellenic elements in Christianity. Patterns can be transformed, but the observational view will still be able to identify their lineage. The developed model allows a deeper understanding of the culture of both ancient societies, as well as the outlook of Western man.